(untitled) - Johnson, Lyndon B. (New York, 1997)
An indispensable window onto one of the most legendary figures on American politics and his tumultuous, controversial years in power, Taking Charge provides an intimate look at a pivotal American presidency--in Lyndon Johnson's words, history "with the bark off." of photos. Website feature.
Keywords: Politics and government; Sources; 1963-1969; United States